Oil Soluble Corrosion Inhibitor on Microbiologically Influenced Corrosion in Diesel Transporting Pipeline - Muthukumar,N. (2007)
The effect of oil soluble commercial corrosion inhibitors (OSCI) on the growth of bacteria and its corrosion inhibition efficiency were investigated. Corrosion inhibition efficiency was studied by rotating cage test and the nature of biodegradation of corrosion inhibitor was also analyzed by using FTIR, NMR and GC-MS. This isolate has the capacity to degrade the aromatic and aliphatic hydrocarbon present in the corrosion inhibitors. The degraded products of corrosion inhibitors and bacterial activity determine the electrochemical behaviour of API 5LX steel. The influence of bacterial activity on degradation of corrosion inhibitor and its influence on corrosion of API 5LX have been evaluated by employing weight loss techniques and electrochemical studies. The present study also emphasizes the importance of evaluation of oil soluble corrosion inhibitor in stagnant model (flow loop test) and discusses the demerits of the oil soluble corrosion inhibitors in petroleum product pipeline.